Valid Competency Assessment in Higher Education: Framework, Results, and Further Perspectives of the German Research Program KoKoHs. (January 2017) - Zlatkin-Troitschanskaia, Olga; Pant, Hans Anand; Toepper, Miriam; Lautenbach, Corinna; Molerov, Dimitar
The aim of the 15 collaborative projects conducted during the new funding phase of the German research program Modeling and Measuring Competencies in Higher Education—Validation and Methodological Innovations (KoKoHs) is to make a significant contribution to advancing the field of modeling and valid measurement of competencies acquired in higher education. The KoKoHs research teams assess generic competencies and domain-specific competencies in teacher education, social and economic sciences, and medicine based on findings from and using competency models and assessment instruments developed during the first KoKoHs funding phase. Further, they enhance, validate, and test measurement approaches for use in higher education in Germany. Results and findings are transferred at various levels to national and international research, higher education practice, and education policy.